2004
DOI: 10.1002/mds.20247
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged practice is of scarce benefit in improving motor performance in Parkinson's disease

Abstract: Many studies have addressed practice effects in motor sequences in Parkinson's disease (PD). Most studied short-term practice and showed that treated patients with mild-to-moderate disease achieve normal or slightly abnormal improvement. Less attention has focused on practice effects after prolonged training (days), and the results are inconclusive. Here, we studied the kinematic changes induced by prolonged practice in a group of medicated patients with mild-to-moderate PD and a healthy control group. We did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
36
0
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 42 publications
4
36
0
4
Order By: Relevance
“…A number of studies have investigated the importance of the striatal system for retention of implicit skills. Studies which examined procedural skills over one session or over a few days found good retention by PPD (Harrington, Haaland, Yeo, & Marder, 1990;Rostami & Ashayeri, 2009), while those that looked over months of practice found increasing differences in skill retention between PPD and control participants (Agostino et al, 2004;Doyon et al, 1998;Kawai, Kawamura, & Kawachi, 1999;Mochizuki-Kawai, Kawamura, Hasegawa, Mochizuki, Oeda, Yamanaka, & Tagaya, 2004;Vakil & Herishanu-Naaman, 1998).…”
Section: Retention Of Implicit Learning In Ppdmentioning
confidence: 95%
“…A number of studies have investigated the importance of the striatal system for retention of implicit skills. Studies which examined procedural skills over one session or over a few days found good retention by PPD (Harrington, Haaland, Yeo, & Marder, 1990;Rostami & Ashayeri, 2009), while those that looked over months of practice found increasing differences in skill retention between PPD and control participants (Agostino et al, 2004;Doyon et al, 1998;Kawai, Kawamura, & Kawachi, 1999;Mochizuki-Kawai, Kawamura, Hasegawa, Mochizuki, Oeda, Yamanaka, & Tagaya, 2004;Vakil & Herishanu-Naaman, 1998).…”
Section: Retention Of Implicit Learning In Ppdmentioning
confidence: 95%
“…[6] Retention reflects how the kinematic improvement is maintained after ending of the practice. [3] In the present study, maintenance of the performance level after one-week retention period indicated a learning effect of motor skill practice. Movement variables responsible for retention may be encoded in a motor representation stored in distributed network of cortical motor area, including the primary motor, premotor, and parietal cortex.…”
Section: Discussionmentioning
confidence: 84%
“…[25] Normal learning retention in people with PD may be demonstrated so that during execution of movements, some of the motor areas of cortex show hyperactivity, reflecting an attempt to compensate basal ganglia dysfunctions. [3] From a clinical and rehabilitation viewpoint, although we may not be able to generalize the results of our Beck depression inventory mini-mental state examination Parkinsonُs disease unified Parkinsonُs disease rating scale simple task to the complex daily performances, our finding that patients with mild to moderate PD can improve with motor skill practice, may be helpful in considering practice as a critical method and an effective rehabilitation intervention to decrease bradykinesia. [3,4,6] It should be mentioned that further follow-up studies on advantages at longer terms of motor skill practice and longer retention periods is warranted.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations